Screening for congenital heart defects: diversified strategies in current China. Issue 1 (21st May 2019) - Liu, Xiwang; Xu, Weize; Yu, Jiangen; Shu, Qiang
Abstract : Background: Congenital heart defects (CHD) is the most common type of birth defect and a leading cause of infant mortality in China. Detection of CHD during newborn is still challenging. The contradiction between the increasingly mature technology of diagnosis and treatment and the inability of early detection is the biggest current dilemma. A few pilot studies attempt to establish the universal screening for CHD in newborns; however, the rate of misdiagnosis is still high in most Chinese hospitals, especially in some undeveloped middle-western regions. Data sources: Based on the recent publications on screening of congenital heart diseases in China. We reviewed the use of diversified screening strategies in current China. Results: Prenatal diagnosis by fetal echocardiography and postnatal detection by pulse oximetry combined with clinical assessment are the useful methods for CHD screening in most areas. The altitude should be taken into account when using pulse oximetry in the middle-western areas of China, where the incidence of CHD maybe higher. Echocardiography is suitable for CHD screening in almost all areas but it could add to financial burden in the developing regions. Genetic analysis could assist clinical doctors to perform more earlier screening and give better counseling regarding the outcome. Due to disparities in economic and medical resources, the screening system should be carried out from multiple perspectives according to the present economic development. Notably, follow-up is an important issue in the screening of CHD, especially for the asymptomatic babies who discharged home. Policies should be formulated to address the epidemiology of CHD in deprived areas to better allocate medical resources and to develop local training programmes to screen and diagnose CHD. Conclusions: Diversified strategies are available in current China. The two-indicator method for CHD screening is recommended to be implemented in routine postnatal care. We can do more in screening for CHD in the future.